Selvitys toisen tai useamman korkeakoulututkinnon suorittaneista - Hanna Virtanen; Pekka Vanhala (The Research Institute of the Finnish Economy (ETLA), 2023)
– This brief provides descriptive evidence on completion of multiple higher education degrees in Finland. In the year 2020, there were altogether 7,100 individuals enrolling in higher education who already had higher education degrees. A quarter of them already had more than one higher education degree. The share of those with prior degrees participating in higher education has been increasing sharply during the past two decades. In the year 2020, ten percent of all new students in higher education had already completed higher education previously. The most common education choice among these students was the field of Health and Welfare in Universities of Applied Sciences. According to the analysis, students with prior degrees took almost as long to complete the degree when compared to those who were completing their first degree. Women and those whose mother tongue is Finnish are vastly over-presented among those completing multiple degrees. Additionally, these students are performing fairly well in the labor market before returning to higher education. Completing multiple degrees does not lead to higher income or better employment even in the medium term. There is a drop in the labor market outcomes following the new enrollment in higher education; however, they bounce back to their previous level in a few years. After that, the labor market performance follows a very similar trend to what it was before enrollment.
Keywords: I21; I23; J31; 330; Higher education; Employment; Earnings